From Policies to Practices: A Proposed Standardized Inclusive Education Readiness Test for Teachers - Tamse, Mitze Gay; Ramos, Kevin Arman; Marquez, Ma. Shienna; Valenzuela, Ruth; Caguioa, Erlinda (International Journal of Sustainability and Advanced Integrated Research, 2026)
The actual implementation of inclusive education is most evident in classroom instruction, where teachers play a critical role in addressing learner diversity. This study aimed to develop and validate the Inclusive Education Readiness Test (IERT), a standardized tool designed to assess Filipino teachers’ preparedness to manage inclusive classrooms. Grounded in the Universal Design for Learning (UDL) framework—focusing on Engagement, Representation, and Action & Expression—the study aligned these principles with local and international standards for inclusive education, including DepEd Order No. 21, s. 2019 (Department of Education, 2019) and Republic Act No. 11650 (Department of Education, 2019; Republic of the Philippines, 2022). A sequential exploratory mixed-methods design was employed, beginning with a qualitative literature review to identify key frameworks, practices, and indicators in inclusive education, followed by quantitative instrument development and expert validation. Four educational experts, selected based on their experience in curriculum design, inclusive education, and leadership roles, assessed the tool using the Content Validity Index (CVI) at both item and scale levels, supplemented by criterion-level evaluation to ensure clarity, relevance, and alignment with policy and theoretical frameworks. Results indicated that teachers generally demonstrate moderate to high readiness in valuing learner diversity, facilitating learning content and pedagogy, pursuing personal and professional development, and working collaboratively with stakeholders. However, challenges remain in practical application, institutional support, and technology integration, highlighting the need for structured professional development and policy alignment. The IERT serves as a reflective and evidence-based instrument for educators, supporting more equitable and effective inclusive education practices. The study contributes to Sustainable Development Goal (SDG) 4 on Quality Education by enhancing teacher capacity to provide inclusive learning opportunities and SDG 10 on Reduced Inequalities by promoting equitable participation for all learners. Its sustainability impact lies in strengthening teacher competence, improving institutional readiness, and fostering community engagement, ensuring long-term implementation of inclusive education practices in Philippine classrooms.